Fodor's northern California - Crabtree, Cheryl; Kast-Myers, Marlise; Mangin, Daniel (Fodor's Travel, a division of Internet Brands, Inc., 2024)
Whether you want to get a glimpse of the Golden Gate Bridge, wander among giant redwood trees in Sequoia National Park, or camp in Yosemite Valley, the local Fodor's travel experts in Northern California are here to help! Fodor's Northern California guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time.